(untitled) (NAU Journal of Technology and Vocational Education, 2025)
This study examined the effect of mobile learning applications on the academic achievement of senior secondary school students in Physics in Ogbia LGA, Bayelsa State. A quasi-experimental design was employed using 180 SS II students, divided into an experimental group taught with mobile learning applications and a control group taught with the lecture method. Data were collected using a Physics Achievement Test (PAT) and analyzed with mean, standard deviation, and z-tests at 0.05 significance level. Findings showed that students taught with mobile learning applications achieved significantly higher scores than those taught traditionally. Gender analysis revealed no significant difference between male and female students, indicating that both groups benefited equally. The study concludes that mobile learning applications enhance Physics learning outcomes and recommends their integration into secondary school instruction to improve achievement and promote equitable access to quality science education.